Wycena korzyści społecznych budowy parków wiatrowych jako szansa aktywizacji regionów wiejskich - Pultowicz, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Renewable energy sources, especially wind energy, are corresponding to the concept of sustainable development. Wind energy as a clean, free and environmental safe source of power is one of the significant factors which can enhance activity on rural areas. This kind of renewables can be a great chance to create new work places and improve prosperity of impoverished rural areas. This paper analyzes and assesses social advantages of building wind farms on rural areas, which is a new subject in ecological economic theory. The analysis is based on the research conducted by the author in 2005 in Cisowo and Kopań in Darłowo commune. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 113-119